The Oxford handbook of open innovation - Chesbrough, Henry William,; Radziwon, Agnieszka,; Vanhaverbeke, Wim,; West, Joel, (Oxford handbooks online., 2023)
This handbook seeks to be the definitive reference for the large and growing field of open innovation.